Axotomy Induces Drp1-Dependent Fragmentation of Axonal Mitochondria - Kedra, Joseph; Lin, Shen; Pacheco, Almudena; Gallo, Gianluca; Smith, George M. (Frontiers in Molecular Neuroscience, 2021)
It is well established that CNS axons fail to regenerate, undergo retrograde dieback, and form dystrophic growth cones due to both intrinsic and extrinsic factors. We sought to investigate the role of axonal mitochondria in the axonal response to injury. A viral vector (AAV) containing a mitochondrially targeted fluorescent protein (mitoDsRed) as well as fluorescently tagged LC3 (GFP-LC3), an autophagosomal marker, was injected into the primary motor cortex, to label the corticospinal tract (CST), of adult rats. The axons of the CST were then injured by dorsal column lesion at C4-C5. We found that mitochondria in injured CST axons near the injury site are fragmented and fragmentation of mitochondria persists for 2 weeks before returning to pre-injury lengths. Fragmented mitochondria have consistently been shown to be dysfunctional and detrimental to cellular health. Inhibition of Drp1, the GTPase responsible for mitochondrial fission, using a specific pharmacological inhibitor (mDivi-1) blocked fragmentation. Additionally, it was determined that there is increased mitophagy in CST axons following Spinal cord injury (SCI) based on increased colocalization of mitochondria and LC3. In vitro models revealed that mitochondrial divalent ion uptake is necessary for injury-induced mitochondrial fission, as inhibiting the mitochondrial calcium uniporter (MCU) using RU360 prevented injury-induced fission. This phenomenon was also observed in vivo. These studies indicate that following the injury, both in vivo and in vitro, axonal mitochondria undergo increased fission, which may contribute to the lack of regeneration seen in CNS neurons.